The identity of Coniogramme wilsonii (Pteridaceae) - Zhao, Junwen; Yang, Wenli; Wang, Caihong; Zhang, Gangmin (Phytotaxa, 2018)
Most of Chinese specimens identified as Coniogramme wilsonii were actually C. fauriei. Based on field observation on C. sinensis around the type locality, type examination, and a review of the literature, C. sinensis is proposed as a synonym of C. wilsonii.